2020
DOI: 10.1186/s12888-020-02909-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening for depressive symptoms in cardiovascular patients at a tertiary centre in Trinidad and Tobago: investigation of correlates in the SAD CAT study

Abstract: Background This study aimed to screen cardiovascular patients for depressive symptoms at a tertiary centre in Trinidad and Tobago; and to determine any significant associations amongst patients’ demographics, comorbidities, and cardiovascular medications with depressive symptoms. Methods In this observational, cross-sectional study, patients (n = 1203) were randomly selected from the cardiology outpatient clinics at the Eric Williams… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
2
15
0
1
Order By: Relevance
“…This study revealed a significantly higher risk of depression among females than males, which is concordant with previous studies' findings [ 33 , 37 , 38 , 64 , 65 ]. Some studies reported a 1.7-fold higher incidence and prevalence in women [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed a significantly higher risk of depression among females than males, which is concordant with previous studies' findings [ 33 , 37 , 38 , 64 , 65 ]. Some studies reported a 1.7-fold higher incidence and prevalence in women [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…Three synthesized themes were identified: (1) prevalence of comorbid mental health problems and chronic NCDs ( n = 10); [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]; (2) factors that mitigate or mediate the association between mental health problems and chronic NCDs ( n = 11) [ 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 ]; —(2a) factors influencing self-management ( n = 4); [ 26 , 27 , 29 , 30 ]; (2b) association between mental health and NCD outcomes—studies focused on (2b1) risk factors ( n = 9) [ 23 , 24 , 25 , 26 , 27 , 28 , 31 , 32 , 33 ]; and (2b2) protective factors ( n = 3); [ 24 , 31 , 33 ]; and (3) varied results ( n = 3) [ 27 , 28 , 29 ]. The results are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Comorbid poor mental health and chronic NCDs were reported throughout the literature, with 7 out of 14 studies reporting a statistically significant association between mental health problems (e.g., depression) and comorbid NCDs in African Caribbeans [ 21 , 22 , 23 , 24 , 25 , 26 , 30 ]. Stewart et al reported a strong association between depression and physical illness and subsequent disability (e.g., stroke) in the African Caribbean population (OR = 2.48) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the relatively low prevalence of T2DM in this study (15%) compared with other local studies of bordering almost 50%, no adjusted analyses were performed to assess the effects of this metabolic condition on native CA size. 10 60 As aforementioned, T2DM is implicated in negative remodelling, resulting in smaller CA size and may allude to heterogeneous results. The study also did not adjust for cardiovascular medications, which may impact CA sizes, such as calcium channel blockers and long-acting nitrates.…”
Section: Discussionmentioning
confidence: 99%